Against the science of law: an alternative to its study and application - Huanca Villalta, Juan Jose (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article elaborates an interpretive and polemic on the study of law, starting from different coordinates to that of legal science in order to postulate an alternative to the understanding of law. For this work, we problematize and detach ourselves from its valuation as a science. We take as a basis the philosophical orientation that views science from the materialistic perspective of the Theory of Categorial Closure, in order to subsequently examine and conceive law as a techno-praxis in relation to the three-dimensional theory as a conceptual framework, thus allowing to consolidate an usable project at the service of the legal researcher.